Outflow graft obstruction in patients with the HM 3 LVAD: A percutaneous approach. Issue 7 (28th May 2021) - Milwidsky, Assi; Alvarez Villela, Miguel; Wiley, Jose; Sanina, Cristina; Patel, Snehal R.; Sutton, Nicole; Latib, Azeem; Sims, Daniel B.; Forest, Stephen J.; Shin, Julia J.; Farooq, Muhammad U.; Goldstein, Daniel J.; et al.
Abstract: Background: The use of the HeartMate 3 (HM3) left ventricular assist device (LVAD) is expanding. Despite being associated with lower rates of adverse events and increased survival, outflow graft obstruction (OGO) has been reported in patients with HM3. The incidence and best management of this serious complication remain unclear. Methods: We describe six cases of HM3 OGO occurring in five patients in our institutional HM3 cohort. Four cases underwent computed tomography angiography and in two percutaneous angiography was directly performed to confirm the diagnosis. In four cases, percutaneous repair of the OG was performed using common interventional cardiology (IC) techniques. Results: Our institutional incidence of OGO was 7% (event rate of 0.05 per patient year); much higher than the previously reported incidence of 1.6%. All cases occurred in the bend relief covered segment. Only two patients had apparent OG twisting, and in two, OGO occurred despite placement of an anti‐twist clip at the time of implant. External compression seems to play a role in most cases. Balloon "graftoplasty" and stent deployment via the femoral artery alleviated the obstruction and normalized LVAD flow in all patients who underwent percutaneous repair. The use of self‐expanding stents allowed for downsizing of the procedural access site to 10 Fr. No serious procedure‐related complications occurred. Conclusion: OGO is common in HM3 patients, external compression due to biomaterial accumulated surrounding the OG is a common etiology. Percutaneous repair using standard IC techniques is safe and feasible in cases of compression with or without partial twisting.